Bohater reklamowy, czyli jak budować wiarygodność w reklamie - Kozłowska, Anna (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2013)
The article is the result of the review of the literature concerning advertising, persuasion, social influence, etc. A hero is someone reliable that can be trusted and/or who has knowledge on the subject. In conclusion the text presents methods in which that kind of character is used in advertisements. An average consumer who knows the product from his personal experience is more oft en a main character of an ad than a professional who is highly knowledgeable because of his training and work. Ads usually present an emotional woman as an average consumer and rational man as an expert with knowledge and experience backed with affiliation with scientific institutions and association.